Analisis Pola Asuh Orang Tua Terhadap Perkembangan Kepercayaan Diri Anak - Rahmah Putrie Meilani; Safuri Musa; Ratna Sari Dewi (Jurnal Ilmiah Wahana Pendidikan, 2022)
This study aims to: (1) describe the application of parental custody patterns to the development of child confidence (case study at PAUD Arbagani Sam Karawang). (2) Describing the results of parental custody patterns on the development of child confidence (case study at PAUD Arbagani Sam Karawang). This study used a qualitative approach with a case study method. The subjects of this study consisted of principal, teacher, and parents at PAUD Arbagani Sam Karawang. Data collection is done using observation, interview, and documentation methods. The results of this study show that (1) The application of parental custody patterns to the development of children's confidence is by directly accompanying the child's development, giving appreciation to the child after the child has finished doing something, and supporting the child's potential. (2) The result of parental custody patterns on the development of the child's confidence can be said to be quite good because the child is already able to socialize with others and is not ashamed to show the ability that exists in the child.